Nitrosative stress induced by homocysteine thiolactone drives vascular cognitive impairments via GTP cyclohydrolase 1 S-nitrosylation in vivo - Ya-Ling Yin; Yuan Chen; Feng Ren; Lu Wang; Mo-Li Zhu; Jun-Xiu Lu; Qian-Qian Wang; Cheng-Biao Lu; Chao Liu; Yong-Ping Bai; Shuang-Xi Wang; Jian-Zhi Wang; et al. (Redox Biology, 2022)
Background: s: Hyperhomocysteinemia (HHcy) is one of risk factors for vascular cognitive impairment (VCI). GTP cyclohydrolase 1 (GCH1) deficiency is critical to oxidative stress in vascular dysfunction. The aim of this study was designed to examine whether HHcy induces VCI through GCH1 S-nitrosylation, a redox-related post-translational modification of cysteine. Methods: The VCI model was induced by feeding mice homocysteine thiolactone (HTL) for 16 consecutive weeks. The cognitive functions were evaluated by step-down avoidance test, passive avoidance step-through task test, and Morris water maze (MWM) test. Protein S-nitrosylation was assayed using a biotin-switch method. Results: In cell-free system, nitric oxide (NO) donor induced GCH1 protein S-nitrosylation and decreased GCH1 activity. In endothelial cells, HTL increased GCH1 S-nitrosylation, reduced tetrahydrobiopterin, and induced oxidative stress, which were attenuated by N-acetyl-cysteine, L-N6-1-Iminoethyl-lysine, mutant of GCH1 cysteine 141 to alanine (MT-GCH1) or gene deletion of inducible NO synthase (iNOS). Further, HTL incubation or iNOS overexpression promoted endothelial cellular senescence, but abolished by exogenous expression of MT-GCH1 or pharmacological approaches including N-acetyl-cysteine, L-sepiapterin, and tempol. In wildtype mice, long-term administration of HTL induced GCH1 S-nitrosylation and vascular stiffness, decreased cerebral blood flow, and damaged the cognitive functions. However, these abnormalities induced by HTL administration were rescued by enforced expression of MT-GCH1 or gene knockout of iNOS. In human subjects, GCH1 S-nitrosylation was increased and cognitive functions were impaired in patients with HHcy. Conclusion: The iNOS-mediated nitrosative stress induced by HTL drives GCH1 S-nitrosylation to induce cerebral vascular stiffness and cognitive impairments.